Faktor-Faktor yang Memengaruhi Kejadian Plebitis di Ruang Marwah RSU Haji Surabaya - Sukadiono Sukadiono; Ika Novianti; Musrifatul Uliyah; Dede Nasrullah (Universitas Muhammadiyah Surabaya, 2019)
Intravenous therapy is the installation of an invasive device into a vein during a patient undergoing treatment in the hospital. One of the complications of intravenous therapy 5% - 70% is the incidence of plebitis. The incidence of plebitis in government hospitals is 50.11%. In Haji Hospital Surabaya, the incidence of plebitis is a problem in patients who receive intravenous therapy in the hospital. The purpose of this study is to analyze the existence of factors that influence the incidence of plebitis. Methods: this study uses analytic design that is observational. The population was all patients who received intravenous therapy in the Marwah Room of the Hajj Hospital Surabaya. The sample of the research by probabability sampling is simple random sampling design with 82 respondents. Research variables include age, location of installation, type of fluid and duration of infusion. The instruments used were interviews and document studies. Data analysis using Linear Regression test with R Square = 0.3 and significance significance α = 0.05. Result & Discussion: The results of the study of age (0.345), and the type of infusion fluid (0.305) had no influence on the incidence of plebitis, whereas the location of infusion (0.020), and the length of day of infusion (0.000) influenced the incidence of plebitis. Conclusions from the study of the location of the installation factors and the duration of infusion installation affect the incidence of plebitis. Thus it is necessary to hold training related to how to prevent plebitis.